Efek Staebler-Wronski dan Pengaruh Waktu Anil pada Lapisan Instrinsik Silikon Amorf Terhidrogenasi (a-Si:H): Yoyok Cahyono, Fuad D. Muttaqin, Umi Maslakah, Malik A. Baqiya, Mochamad Zainuri, Eddy Yahya, Suminar Pratapa, Darminto Darminto - Yoyok Cahyono Yoyok Cahyono; Fuad D. Muttaqin Fuad D. Muttaqin; Umi Maslakah Umi Maslakah; Malik Anjelh Baqiya Malik Anjelh Baqiya (Jurnal Fisika dan Aplikasinya, 2017)
Hydrogenated amorphous silicon (a-Si:H) is one of the most promising solar cell materials, as compared to the crystalline silicon (c-Si). This material has a greater absorption with less material requirement (thin). So it is expected to reduce the cost of production and price of solar cells. But until now there are still many unresolved issues, especially with regard to low efficiency, and the Staebler-Wronski effect. This study aims to describe the effect of Staebler-Wronski, which is the effect of long-time exposure to heat on the layer of solar cell material by means of annealing treatment. The results show that the longer annealing time, there is a tendency to decrease transmittance, which is thought to be caused by changes in crystallinity, energy band gap, Urbach energy and particle size. The increasing annealing time can lead to the release of hydrogen bonds that cause an increase in localized state, due to the activation of the dangling bond which is the main cause of the Staebler-Wronski effect.